2004
DOI: 10.5038/2375-0901.7.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Crime and Fear of Crime While Waiting at Britain’s Railway Stations

Abstract: Crime on the railways in Britain is an increasing concern for train operating compa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 8 publications
0
39
1
6
Order By: Relevance
“…Similar studies have examined over ground rail stations in the country Wales (Cozens et al, 2004). A clear finding from these studies, particularly in relation to the Washington DC example, was how unusually low crime rates (compared to other systems and local crime rates) could be explained by reference to aspects of environmental design.…”
Section: Crime At Stops and Stationsmentioning
confidence: 85%
“…Similar studies have examined over ground rail stations in the country Wales (Cozens et al, 2004). A clear finding from these studies, particularly in relation to the Washington DC example, was how unusually low crime rates (compared to other systems and local crime rates) could be explained by reference to aspects of environmental design.…”
Section: Crime At Stops and Stationsmentioning
confidence: 85%
“…Perceptions of safety are influenced by many factors, including the built environment and the design of railway stations (Gilling 1997;Smith and Clarke 2000;Schmucki 2002;Cozens et al 2002Cozens et al , 2003aCozens et al , 2003bCozens et al , 2004Smith 2008;Sorensen, Hayes, and Atlas 2008;Vilalta 2011;Delbosc and Currie 2012). Thus, it follows that good environmental design may decrease crime and fear of crime.…”
Section: Crime Prevention Through Environmental Design (Cpted)mentioning
confidence: 99%
“…Although "crime on public transport is relatively rare" (Batley et al 2014, 33), research has demonstrated consistently that crime and fear of crime can affect levels of patronage (Crime Concern 1997Cozens et al 2004;Delbosc and Currie 2012). Patronage levels could be more than 10% higher if people felt more secure when traveling and waiting at railway stations (Crime Concern 2002.…”
Section: Introductionmentioning
confidence: 99%
“…A key feature of many transit nodes, be it stops or stations, is that they have been designed, or redesigned, to incorporate a number of the principles of designing out crime (La Vigne 1997, Cozens 2004, Liggett et al, 2004. Many rail stations in the UK for example, aim to conform to the Secure Stations Scheme, based on the Secured by Design award principles, and managed by the Department for Transport (DfT) and British Transport Police (BTP).…”
Section: Micro Transit Environments and The Transit Nodementioning
confidence: 99%
“…Whilst there has been a large volume of research into both perception and fear of crime in general, there is a paucity of studies that apply this research specifically to transport systems. Some noticeable exceptions include Atkins, 1990;Cozens, 2004;and Smith 2008. These are explored in more detail in Part Five of this book.…”
Section: The User Perspectivementioning
confidence: 99%